Assessing Urban Level Changes Using GIS and Statistical Analysis in the Kedungsepur Metropolitan, Indonesia - Indrayati, Ariyani; Rijanta; Muta'ali, Luthfi; Rachmawati, Rini (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2024)
From 2010 to 2020, the Kedungsepur Metropolitan Corridor experienced spatial transformations, converting agricultural areas into built-up areas. This study seeks to identify new insights by examining the correlation between socioeconomic facilities and built-up areas, typically analyzed separately. Satellite imagery interpretation was used to determine the proportion of built-up areas, apply the K-Means Cluster method for the urban level, and conduct statistical analysis using the chisquare test. The findings reveal that the Semarang—Ungaran—Salatiga Corridor has the greatest built-up areas. The average change in built-up area within the Kedungsepur Metropolitan Corridor from 2010 to 2020 was 3.25%. Additionally, the Central Semarang Subdistrict had the highest level of socioeconomic facilities. However, the Chi-Square test results indicated differences between the observed and expected frequencies of built-up area percentages in each subdistrict for both 2010 and 2020. Surprisingly, no correlation was found between urban-level changes related to built-up areas and socioeconomic facilities. These results suggest that urban changes in the primary city are relatively stagnant, while more intensive development occurs in secondary cities withinKedungsepur. The dominant driving factor for urban transformation is the change in built-up areas,which indicates the intensified growth of secondary cities.